To Determine the Frequency of Silent Myocardial Ischemia in Type-II Diabetic Patients with Proteinuria (Medical Forum Monthly, 2024)
Objective: To determine the frequency of silent myocardial ischemia in type-II diabetic patients with proteinuria.Study Design: Cross sectional study.Place and Duration of Study: This study was performed at Department of Medicine in collaboration with department of Cardiology CMC, Hospital larkana from 15-Nov-2011 to 14-May-2012.Materials and Methods: There was a non probability purposive sampling. All patients who were type-II diabetics and having proteinuria were included in this study. The age of these patients were > 35 years. They were selected for determination of silent myocardial Ischemia. The electrocardiography of all those patients having FBG>126 mg/dl and proteinuria > 150mg/dl was performed. The ETT of all patients was done in cardiology department. Those patients who have normal ETT were labeled negative for silent myocardial ischemia, while ETT positive patients were labeled as having silent myocardial ischemia.Results: The total no: of 323 patients were included in this study with mean age of 49.9+10.3 years, 270 (83.6%) were male and 53 (16.4%) were female. The ETT was positive in 69 (21.36%) patients.Conclusion: The frequency of SMI in our study was 21.36%.